PARIWISATA TANPA EKSPLOITASI: PRAKTIK CORPORATE SOCIAL RESPONSIBILITY DI KEBUN BINATANG JATIM PARK 2, JAWA TIMUR - Ahmad Sholihudin; Nurita Andriani (JURNAL LENTERA BISNIS, 2023)
This study aimed to analyze the Corporate Social Responsibility (CSR) practices implemented at Jatim Park 2 Zoo, East Java, focusing on the executed CSR programs and their impacts on the environment, local communities, and various associated stakeholders. The research method employed was descriptive-qualitative, utilizing data collection through documentary studies sourced from the official website profiles and programs of Batu Secret Zoo, along with coverage from mass media. The data analysis technique adopted was the Miles and Huberman method. The findings indicated that Batu Secret Zoo had been actively engaged in CSR practices through conservation, education, and wildlife protection programs, resulting in a positive impact on the environment and raising awareness among communities regarding the significance of environmental conservation. However, challenges existed in evaluating comprehensive impacts and expanding CSR programs to be more inclusive and sustainable. The implications of this research provide in-depth insights into the effectiveness of CSR practices within the tourism sector and offer recommendations to enhance holistic CSR implementation in similar tourism destinations in the future. Keywords: CSR; Tourism; Zoo